2015
DOI: 10.1007/s11695-015-1668-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after Bariatric Surgery: Obstetric and Perinatal Outcomes and the Growth and Development of Children

Abstract: Except for the large index of low birth weight, it can be concluded that pregnancy after bariatric surgery is safe. The growth rate was found to be adequate in the children born after the surgery, with reduced obesity. Although changes in speech development were detected, no factors were supported an association with pregnancy after bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
0
13
0
2
Order By: Relevance
“…On the contrary, a reduced weight gain is associated with prematurity and low birthweight. Pregnant women who present an insufficient weight increase should be subject to more frequent monitoring of fetal growth . In this study, 15 out of 34 (44.1%) pregnant women presented a weight gain that was higher than that recommended.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…On the contrary, a reduced weight gain is associated with prematurity and low birthweight. Pregnant women who present an insufficient weight increase should be subject to more frequent monitoring of fetal growth . In this study, 15 out of 34 (44.1%) pregnant women presented a weight gain that was higher than that recommended.…”
Section: Discussionmentioning
confidence: 79%
“…As with GDM, most studies report that pregnant women who have had BS have a lower risk of developing pre‐eclampsia when compared to obese women not undergoing BS . There is also a reference to a reduced risk of developing eclampsia, gestational hypertension, and complications related to chronic hypertension . A meta‐analysis revealed that in pregnant women post‐BS, there is a 50% reduction in the risk of developing GDM or hypertensive problems when compared to a non‐BS obese control group .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrauterine growth restriction (IUGR) is increased by 2-3 fold after bariatric surgery (15, 38). In addition, pregnancies in women who had undergone procedures such as Roux-en-Y gastric bypass or RYGB, had a greater risk for SGA in comparison to weight loss procedures that such as LAPBAND, including VSG (11).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported decreased risk of GHT and pre‐eclampsia in women who had undergone bariatric surgery when compared with obese pregnant women . In a meta‐analysis, Yi et al .…”
Section: Discussionmentioning
confidence: 99%